The Influence of Meteorological Factors on Osteoarthritis Symptoms and Physical Activity: A Narrative Review - Strašunskas, Karolis; Mikalauskas, Matas; Montvydaitė-Kreivaitienė, Ona (Acta medica Lituanica, 2026)
Background: Meteorological conditions are suspected to influence osteoarthritis (OA) symptoms, but findings across climates and populations are inconsistent. Understanding how temperature, humidity, and barometric pressure affect pain, stiffness, and physical activity is relevant for clinical counselling and study design. Objective: To synthesize recent evidence on associations between natural weather variation and OA symptomatology, including impacts on physical activity and rehabilitation participation. Methods: We searched PubMed, ScienceDirect, and Google Scholar for peer-reviewed human studies published from January 2010 to May 2024 by using terms related to osteoarthritis and meteorological factors (temperature, humidity, barometric pressure, precipitation, seasonal variation) combined with pain, stiffness, function, or physical activity. Inclusion criteria comprised clinically or radiographically confirmed OA and quantitative outcomes linked to measured meteorological exposures. Interventional artificial heat/cold studies and non-primary data were excluded. Two reviewers independently screened, selected, and extracted data with consensus resolution. Results: Temperature showed the most consistent patterns: colder and more variable conditions were linked to increased pain and stiffness, whereas warmer, stable conditions favored mobility. Humidity and barometric pressure fluctuations showed modest effects, particularly under cool and damp conditions. Precipitation, sunlight, and wind had minimal or inconsistent associations. Adverse weather was associated with a reduced outdoor activity and lower rehabilitation participation. Conclusions: Weather acts as a contextual modifier rather than a primary determinant of OA symptoms. Recognizing meteorological influences may aid patient counselling, season-sensitive rehabilitation planning, and the design of outcome studies.